Assessing parents' understanding of Autism Spectrum Disorder (ASD) in Malaysia: a cross-sectional study - Ruth Selvaranee Arunasalam,; Rohana Jani,; Rafidah Aga Mohd Jaladin,; Alias Abd Aziz, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The current understanding of autism among parents of children with Autism Spectrum Disorder (ASD) in Malaysia reflects a multifaceted perspective marked by various challenges including confusion, financial constraints, limited resources, and a shortage of trained special needs teachers and affordable centers. This study aims to assess the level of autism knowledge among parents of individuals with ASD in Malaysia. A cross-sectional study involving 471 parents was conducted in the Klang Valley between May 2022 and June 2023, utilizing an online survey tool. The study found that most parents exhibited limited understanding in crucial areas related to autism such as its causes, diagnosis, and treatment options. Moreover, there was a significant relationship between the level of education and knowledge of ASD. The findings underscore the importance of comprehensive parental training to provide enduring support for children with ASD. This highlights the necessity for ongoing efforts to enhance parental knowledge and support systems for individuals with autism in Malaysia.